AN OPEN-LABEL MULTICENTER OBSERVATIONAL STUDY OF THE EFFICACY, TOLERABILITY, AND SAFETY OF THE NONSTEROIDAL ANTI-INFLAMMATORY DRUG AMTOLMETIN GUACIL IN PATIENTS WITH KNEE OSTEOARTHRITIS AND DYSPEPSIA - E. S. Tsvetkova; L. N. Denisov; A. N. Otteva; A. L. Dubikov; S. P. Yakupova; O. N. Ivanova; N. I. Korshunov; A. R. Vaisberg; R. A. Abyshev; A. V. Tartynov; E. L. Nasonov (Научно-практическая ревматология, 2017)
Objective: to investigate the efficacy and tolerability of amtolmetin guacil (AMG; Niselat®, Dr. Reddy's Laboratories Ltd, India) versus previous therapy with nonsteroidal anti-inflammatory drugs (NSAIDs) in patients with knee osteoarthritis (OA) and signs of dyspepsia.Subjects and methods. The open-label observational study included 220 patients aged 30–65 years who suffered from knee OA and intense pain during NSAID intake and had symptoms of dyspepsia in the absence of contraindications to the use of AMG. Among the comorbidities that generally occurred in 68% of the patients, there was a preponderance of hypertension (42%), lower extremity varicose veins (6.4%), and diabetes mellitus (6%). Treatment efficacy was evaluated using three domains of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), by also taking into account pain intensity and general health assessment on the visual analogue scale. A Severity of Dyspepsia Assessment (SODA) scale was used to rate dyspepsia.Results and discussion. AMG had a marked analgesic effect confirmed by 40% or more pain reduction that occurred in 72.5% of the patients. The high analgesic effect of AMG was confirmed by a statistically significant (p <0.001) reduction in the WOMAC index (pain and stiffness) and by an increase in functional activity. There was a significant decrease in painless and painful signs of dyspepsia, as well as positive changes in the measures “overall assessment of dyspepsia severity” (p < 0.001) and “satisfaction with treatment”. Overall assessment of AMG tolerability was only positive: excellent (33%), good (56%), and satisfactory (11%). There were no serious adverse events (AE). AE were graded as moderate and mild in 8 and 82% of cases, respectively. AE were recorded in 7.7% of the patients. Conclusion. The findings suggest that AMG offers good prospects for knee OA treatment.